AN UNPARALLELED SCHOLAR - Elieva, Nargiza (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
Mirzo Ulugh Beg left a significant scholarly legacy on the Mongol state and the history of the four Uluses. He examined the formation of the Jochi, Chagatai, Ogedei, and Tolui domains, analyzing their political structures and the distribution of power among the descendants of Chinggis Khan. Ulugh Beg organized data on their economic systems, military administration, alliances, and conflicts. His work helps modern researchers understand the reasons behind the empire’s fragmentation and the impact of inter-ulus relations on Central Asian history. His analytical approach remains valuable for today’s historiography.